A XANTHONE FROM THE STEM BARK OF MANGGIS HUTAN (Garcinia bancana) - Muharni Muharni; Dachriyanus Dachriyanus; Husein H. Bahti; Supriyatna Supriyatna (Indonesian Journal of Chemistry, 2007)
A xanthone, 1,5-dihidroxy-3,6-dimethoxy-2,7-bis-(3-methylbutenyl)xanthone had been isolated from the stem bark of Garcinia bancana Miq.  The structure of this compound was elucidated by analysis of spectroscopic data, especially using 1D and 2D NMR spectroscopic data.